Cochrane Database of Systematic Reviews 2002
DOI: 10.1002/14651858.cd003610
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for secondary prevention of coronary heart disease

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the beneficial and harmful effects of antibiotics for the secondary prevention of coronary heart disease. As a secondary objective, we plan to assess the effects of individual types of antibiotics for the secondary prevention of coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We updated our previous meta-analyses [2] with data from the extended follow-up of CLARICOR patients as well as data from new trials identified in January 2007 through searches in The Cochrane Library, PubMed, and EMBASE according to our protocol [7] . Meta-analyses followed the Cochrane Collaboration methodology [7] , including Review Manager [8] for calculation of relative risks with 95% CI with random-effect models and inconsistency ( I 2 ) as a measure of heterogeneity [9] .…”
Section: Statistical Analyses and Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We updated our previous meta-analyses [2] with data from the extended follow-up of CLARICOR patients as well as data from new trials identified in January 2007 through searches in The Cochrane Library, PubMed, and EMBASE according to our protocol [7] . Meta-analyses followed the Cochrane Collaboration methodology [7] , including Review Manager [8] for calculation of relative risks with 95% CI with random-effect models and inconsistency ( I 2 ) as a measure of heterogeneity [9] .…”
Section: Statistical Analyses and Meta-analysesmentioning
confidence: 99%
“…Meta-analyses followed the Cochrane Collaboration methodology [7] , including Review Manager [8] for calculation of relative risks with 95% CI with random-effect models and inconsistency ( I 2 ) as a measure of heterogeneity [9] .…”
Section: Statistical Analyses and Meta-analysesmentioning
confidence: 99%